2018
DOI: 10.5935/0103-507x.20180065
|View full text |Cite
|
Sign up to set email alerts
|

Association between pediatric Risk, Injury, Failure, Loss and End Stage Renal Disease score and mortality in a pediatric intensive care unit: a retrospective study

Abstract: ObjectiveTo evaluate the association between acute kidney injury through the pediatric Risk, Injury, Failure, Loss and End Stage Renal Disease score and mortality in a pediatric intensive care unit.MethodsThis retrospective cohort study assessed all children admitted to the pediatric intensive care unit of a reference hospital in Brazil from January to December 2016. Patients were screened for the presence of acute kidney injury through the pediatric Risk, Injury, Failure, Loss and End Stage Renal Disease scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…When we analyzed the concomitant use of these drugs, the risk of AKI was observed to increase progressively as the number of NTDs used increased. ( 8 , 14 , 16 , 23 , 24 ) McKamy et al, in a retrospective study conducted in a pediatric ICU, identified a 3- to 9-fold increased risk of AKI when vancomycin was used concomitantly with furosemide (p < 0.05). ( 13 ) Our study showed similar results, and this variable was characterized as an independent marker of AKI (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…When we analyzed the concomitant use of these drugs, the risk of AKI was observed to increase progressively as the number of NTDs used increased. ( 8 , 14 , 16 , 23 , 24 ) McKamy et al, in a retrospective study conducted in a pediatric ICU, identified a 3- to 9-fold increased risk of AKI when vancomycin was used concomitantly with furosemide (p < 0.05). ( 13 ) Our study showed similar results, and this variable was characterized as an independent marker of AKI (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%